Analyzing the Impact of Spanish University Funding Policies on the Evolution of Their Performance: A Multi-Criteria Approach. - El-Gibari-Ben-Said, Samira; Pérez Esparrells, Carmen; Gómez-Núñez, Trinidad; Ruiz-de-la-Rúa, Francisco (MDPI, 2021)
The relationship between university performance and performance-based funding models has been a topic of debate for decades. Promoting performance-based funding models can create incentives for improving the educational and research effectiveness of universities, and consequently providing them with a competitive advantage over its competitors. Therefore, this paper studies how to measure the performance of a university through a mathematical multicriteria analysis and tries to link these results with certain university funding policies existing in the Spanish case. To this end, a reference point-based technique is used, which allows the consideration and aggregation of all the aspects regarded as relevant to assess university performance. The simple and easy way in which the information is provided by this technique makes it valuable for decision makers because of considering two aggregation scenarios: the fully compensatory scenario provides an idea of the overall performance, while the non-compensatory one detects possible improvement areas. This study is carried out in two stages. First, the main results of applying the proposed methodology to the performance analysis evolution of the largest three Spanish public university, over a period of five academic years, are described. Second, a discussion is carried out about some interesting features of the analysis proposed at regional level, and some policy messages are provided.
Keywords: Optimización matemática; Universidades - Financiación; Higher education systems; Funding policies; University performance; Multi-criteria techniques; Dynamic analysis